Human Rights Violations and Alleged Crimes War in the Russian-Ukraine Conflict - Wardana, Dodi Jaya; Roqib, Muhammad; Maulana P, Arya (Socio Legal and Islamic Law, 2023)
This research aims to examine human rights violations and alleged war crimes during Russia's invasion of Ukraine. The conflict between Russia and Ukraine occurred because they fought over the Crimea region, Eastern Ukraine. Crimea has been contested for centuries. Crimea was formerly called Tauris or Tavrida, by the Russian people this region is considered the home of various ethnic groups. This conflict between Ukraine and Russia caused many casualties and major damage to physical infrastructure in Ukraine. Russia's actions in the Crimea region have received various criticisms from the European Union and western countries. Russia has intervened in Ukraine and carried out acts of aggression into the Crimea region. The European Union and Western countries condemned Russia's actions as violating the rules of international law. The aim of this research is to determine human rights violations and alleged war crimes in the Russia-Ukraine conflict as well as forms of accountability and sanctions for human rights violations. The research method used is a normative juridical type with a statutory and conceptual approach supported by primary and secondary legal materials. The results of this research show that the United Nations demands that Russia stop its power against Ukraine. Russia, which is involved in the conflict, must comply with the rules and provisions of International Law, which is the only way to resolve Russia's dispute with Ukraine peacefully. Keywords: Russia-Ukraine; Human Rights Violations; War Crimes